Revitalizing Intellectual Property Rights in Indonesia: A Maqasid al-Sharia Perspective on Communal Ownership - Disemadi, Hari Sutra; Al-Fatih, Sholahuddin; Silviani, Ninne Zahara; Rusdiana, Shelvi; Febriyani, Emiliya (Institut Agama Islam Negeri Curup, 2024)
Indonesia's diverse cultural heritage significantly contributes to its economic growth, yet the current intellectual property system, based on Western principles, may not fully align with the country's cultural values. This research aims to enhance the legal framework for Indonesia’s communal intellectual property (CIP), by exploring the potentials brought by of Islamic law, particularly Maqasid al-Shariah. For this purpose, this research utilizes the normative legal research method, analyzing relevant norms within existing laws and Islamic legal doctrines, revealing conceptual correlations between Maqasid al-Shariah and CIP. This research also aims to addresses the common misconceptions regarding Maqasid al-Shariah is crucial for effectively utilizing Islamic law principles in Indonesia's legal system. The analysis demonstrates that communal intellectual property aligns with both Western IP principles and Islamic values, as it recognizes the importance of community welfare and individual benefits. Integrating Maqasid al-Shariah values into Indonesia's CIP legal framework can promote a more inclusive, equitable system that respects collective knowledge and cultural heritage while fostering innovation and creativity.